2020
DOI: 10.1111/eci.13181
|View full text |Cite
|
Sign up to set email alerts
|

Impact of active smoking on the immature platelet fraction and its relationship with the extent of coronary artery disease

Abstract: Introduction:Smoking represents a major cardiovascular risk factor, due to the induction of oxidative stress and low-grade, continuous, inflammation that contribute to promote atherothrombosis. However, the mechanisms leading to increased platelet aggregability associated with smoking are only partially defined. A potential role has been hypothesized for immature platelets, a younger and potentially more reactive fraction, previously associated with the main determinants of coronary artery disease (CAD). There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Interestingly, we found increased immature platelet fraction IPF (IPF>7) in COVID-19-infected subjects, who had evidence of elevated D-dimers and AKI. Immature platelets usually have larger size and are considered to be more reactive and increased IPF has been associated with smokingrelated cardiovascular disease and inflammation [28,29]. Day to day variation in MVP can be related to various factors, including misinterpretation of the true platelet size due to platelets clumps, and some more activated platelets will be consumed in clot formation and not counted by automatic reader.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found increased immature platelet fraction IPF (IPF>7) in COVID-19-infected subjects, who had evidence of elevated D-dimers and AKI. Immature platelets usually have larger size and are considered to be more reactive and increased IPF has been associated with smokingrelated cardiovascular disease and inflammation [28,29]. Day to day variation in MVP can be related to various factors, including misinterpretation of the true platelet size due to platelets clumps, and some more activated platelets will be consumed in clot formation and not counted by automatic reader.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Nardin et al 31 held that smoking was not a contributing factor of CAD, and Akyüz et al 32 found that nonsmokers had a higher tendency than smokers to develop severe CAD. Akyüz et al 32 explained this finding by highlighting that non-smoker CAD patients have higher tumor necrosis factor (cytokine 1A (TL1A)).…”
Section: Discussionmentioning
confidence: 99%
“…Platelet activation is commonly seen in the blood of smokers. Platelets isolated from smokers exhibit spontaneous aggregation ( Nardin et al, 2020 ). After exposure to smoker serum, platelets isolated from non-smokers exhibit a high degree of aggregation ( Pamukcu et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%